2001
DOI: 10.1111/1467-8527.t01-1-00220
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychiatric disorder in children attending a school for pupils with emotional and behavioural difficulties

Abstract: The research presented in this article suggests that young people attending schools for pupils with emotional and behavioural difficulties are more likely to experience concurrent psychiatric disorders (comorbidity) than their peers in mainstream schools. Dr Cassidy (Consultant in Child and Adolescent Psychiatry), Dr James (Consultant and Honorary Senior Lecturer in Child and Adolescent Psychiatry) and Dr Wiggs (Research Psychologist) used questionnaires and interviews with parents and teachers, together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, the SDQ is only a screening tool that indicates the need for further assessment by trained mental health practitioners. These results are similar to those noted by Cassidy et al. (2001) and provide further evidence to support the view that there is a high level of unmet mental health needs among this population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the SDQ is only a screening tool that indicates the need for further assessment by trained mental health practitioners. These results are similar to those noted by Cassidy et al. (2001) and provide further evidence to support the view that there is a high level of unmet mental health needs among this population.…”
Section: Discussionsupporting
confidence: 90%
“…Given the overlap between mental health difficulties, psychiatric disorders and special educational needs, it is not surprising that the severity and complexity of mental health difficulties appears to be higher among pupils attending schools for SEBD. Cassidy, James and Wiggins (2001) found that pupils attending a school for SEBD had higher levels of difficulty on all five subscales of the Strengths and Difficulties Questionnaire (SDQ), when compared with pupils attending mainstream school. Additionally, on four out of five subscales the group attending schools for children with SEBD was rated, or rated themselves, as having significantly more difficulties than the group in mainstream school.…”
Section: Introductionmentioning
confidence: 99%
“…This research was able to assess motor and co-ordination difficulties only in children attending a specialist primary school for SEMH difficulties, and so further research is required to examine the incidence of similar difficulties in children with SEMH in alternative education provisions and in mainstream education. Motor and co-ordination difficulties have been robustly associated with ADHD (Fliers, de Hoog, et al, 2010;, and a high incidence of ADHD amongst children with SEBD has also been reported (Cassidy, James, & Wiggs, 2003;Place, Wilson, Martin, & Hulsmeier, 2000). This study was not designed to examine the association between attention difficulties and SEMH and motor difficulties, but future research could examine this as a method of better understanding some the difficulties displayed by some children with SEMH difficulties across the range of educational contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The perception that children with SEBD tend to have difficulties with attention and listening could reflect the co-occurrence of ADHD and SEBD (Cassidy, James and Wiggs 2001). Data drawn from the questionnaire indicate that few pupils with SEBD are considered by SLTs as having a stammer or speech production difficulties.…”
Section: Communication Difficulties and Sebdmentioning
confidence: 99%